Clinical characteristics of EGFR-ctDNA shedders in EGFR-mutant NSCLC patients - Martina Ruglioni; Iacopo Petrini; Stefania Crucitta; Andrea Sbrana; Giovanna Irene Luculli; Leila Sadeghi Gol; Carola Forte; Antonio Chella; Christian Rolfo; Romano Danesi; Marzia Del Re (Translational Oncology)
Background: Circulating tumor DNA (ctDNA) revolutionized the molecular diagnostics of lung cancer by enabling non-invasive, sensitive identification of actionable mutations. However, ctDNA analysis may be challenging due to tumor shedding variability, leading to false negative results. This study aims to understand the determinants for ctDNA shedding based on clinical characteristics of lung cancer patients, for a better interpretation of false negative results to be considered when ordering ctDNA analysis for clinical practice. Methods: Blood samples were collected from patients with stage IV EGFR-mutated (mEGFR) NSCLC before treatment and monitored until disease progression. EGFR was assessed on tissue by standard procedures, while EGFR status on ctDNA was tested using dPCR at baseline and at the first reassessment. NGS was used to evaluate patients mutational status at the progression of the disease. Results: A total of 40 mEGFR tissue samples were collected. Plasma samples were analyzed for mEGFR before starting the first line, 65 % of patients had detectable mEGFR in ctDNA (“shedders”). Higher ECOG PS (p = 0.04), bilateral localization of primary tumor (p = 0.04), and the presence of intrathoracic/extrathoracic disease (p = 0.05), were associated to mEGFR shedding. Shedders had shorter PFS compared to non-shedders (p = 0.03). Patients with detectable mEGFR in ctDNA at the first radiological assessment exhibited worse PFS compared to patients with ctDNA clearance (p = 0.05). Conclusion: Our preliminary data demonstrate that specific clinical characteristics predict mEGFR shedding in ctDNA of NSCLC, suggesting a potential clinical applicability for understanding potential false negative results and appropriate reporting in clinical practice.